Redefining energy vulnerability, considering the future - Hearn, Adam X.; Mihailova, Darja; Schubert, Iljana; Sohre, Annika (Frontiers in Sustainable Cities, 2022)
Within the EU, energy poverty is believed to affect at least 9.8% of households. Energy poverty can be broadly defined as a households’ inability to meet its energy needs. This is a problem that affects all European countries, but narrow interpretations of data based on notions of material deprivation may lead to energy poverty being overlooked or not considered an issue by policymakers. The EU Energy Poverty Advisory Hub makes a number of essential points when it comes to the measurement, definition, and potential policies and measures to deal with energy poverty. We build on this, using the term energy vulnerability in order to encompass the segment of population identified as living in energy poverty as well as those at risk of becoming energy poor in the future. We use a capabilities approach with a doughnut economics framework to expand on the concept of energy vulnerability as a form of capabilities deprivation, allowing for greater recognition of those that are affected in the present and intergenerationally. This framework is applied using mixed methods consisting of both a Swiss-wide survey of 1486 people and 8 semi-structured interviews with energy stakeholders to investigate the knowledge gap on energy vulnerability in Switzerland. The framework may be applied and have wider repercussions for other parts of the world where energy poverty is not directly addressed, and where using the term of energy vulnerability may help direct policies in a more dynamic and responsive manner. Furthermore, this article identifies some limitations of basing energy vulnerability definitions on data which focuses on material deprivations as this may risk overlooking those that are vulnerable due to other reasons such as building energy efficiency. We find that levels of energy poverty/vulnerability are higher than estimated in official statistics, highlighting the need for tailored policies both in Switzerland and elsewhere. Levels of energy vulnerability in Switzerland may not be reflected elsewhere, but certainly draw attention to the potential misrecognition of energy vulnerability which may be more widespread than previously believed. We examine existing policies that may help to reduce energy vulnerability, as well as suggest other potential mitigation methods.